2017
DOI: 10.1007/s00125-017-4298-z
|View full text |Cite
|
Sign up to set email alerts
|

Bed rest and resistive vibration exercise unveil novel links between skeletal muscle mitochondrial function and insulin resistance

Abstract: Reductions in muscle mitochondrial respiration occur concomitantly with insulin resistance and loss of muscle mass during bed rest and may play a role in the adaptations to physical inactivity. Significantly, we show that RVE is an effective strategy to partially prevent some of the deleterious metabolic effects of bed rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 49 publications
6
42
0
Order By: Relevance
“…In support of this, bed rest has recently been shown to decrease the protein content of the inner mitochondrial membrane ADP transporter, adenine nucleotide translocase (ANT; Kenny et al . ). Moreover, we have previously shown that the ability of submaximal ADP concentrations to decrease mitochondrial hydrogen peroxide emission is impaired in insulin‐resistant rodents (Smith et al .…”
Section: Introductionmentioning
confidence: 97%
“…In support of this, bed rest has recently been shown to decrease the protein content of the inner mitochondrial membrane ADP transporter, adenine nucleotide translocase (ANT; Kenny et al . ). Moreover, we have previously shown that the ability of submaximal ADP concentrations to decrease mitochondrial hydrogen peroxide emission is impaired in insulin‐resistant rodents (Smith et al .…”
Section: Introductionmentioning
confidence: 97%
“…The lack of an association between changes in mitochondrial characteristics and insulin and glucose tolerance was further reinforced by the absence of consistent or strong correlations between these measures. Previous studies examining correlations between these measures in human participants have found correlations between mitochondrial content and insulin resistance [3], but correlations between mitochondrial respiration and insulin resistance have been less consistent [6] [42,43].…”
Section: Discussionmentioning
confidence: 94%
“…However, after adjusting for physical activity and/or trunk fat mass, this relationship between muscle insulin sensitivity and mitochondrial respiration was partially lost and no longer significant [98]. In a study examining bed rest (an extreme form of physical inactivity), there was a positive correlation between mitochondrial respiration and insulin sensitivity [55]. However, on further examination of these findings, this effect may have been due to changes in mitochondrial content rather than changes in respiration [55].…”
Section: Is There a Relationship Between Mitochondrial Respiratory Fumentioning
confidence: 97%
“…In a study examining bed rest (an extreme form of physical inactivity), there was a positive correlation between mitochondrial respiration and insulin sensitivity [55]. However, on further examination of these findings, this effect may have been due to changes in mitochondrial content rather than changes in respiration [55]. Therefore, although some studies have observed parallel changes in mitochondrial respiration and insulin resistance, the relationship between the two appears to be affected by other factors, such as mitochondrial content, physical activity level, and fat mass.…”
Section: Is There a Relationship Between Mitochondrial Respiratory Fumentioning
confidence: 99%